RESTORATION OF BIOMARKER LEVELS IN ISCHEMIC STROKE - Gazieva Sh. R. (Modern American Journals, 2025)
To quickly assess the condition and develop an individual treatment plan in patients with ischemic stroke and low levels of PLA2G2E, DGLA, and PADI4 biomarkers, it is recommended to use the Rankine, Rivermead, MoСА and NIHSS scales. Studies have also established the effectiveness of correcting standard therapy for ischemic stroke by including the nootropic oxiracetam, the dietary supplement GLA, the restoring deficiency of DGLA and the anticoagulant rivaroxaban, which significantly reduce the duration and adverse outcomes of rehabilitation compared with conventional therapy.
Keywords: Ischemic stroke, PLA2G2E, DGLA and PADI4, D-dimer, miR-210.